Sikap Pemirsa terhadap Program Acara Televisi Swasta Nasional - Tulipa, Diyah (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
At the turn of broadcasting growth in Indonesia for the last decade, the competition among private televisions to get audiences is becoming arise too. This paper draws on the correlation between attitude and preference of television's audiences. Moreover, this study measure the attitude of audiences by point ideal which is based on argument that people has ideal value about object some sort of audiences has ideal value about televisions program. Finally, this paper indicates that attitude has positive correlation with preference. It is showed by audience's behavior to see the television's program.